Akcja rządu Clementa Attlee’go na rzecz kontroli energii atomowej (wrzesień-listopad 1945) - Rosiak, Artur (Acta Universitatis Lodziensis. Folia Historica, 1999)
For Clement Attlee the question of the nuclear energy control has become one of the most important in international relations since an American nuclear attack on Hiroshima and Nagasaki in August 1945. British Prime Minister realized the danger created by the fact of invention of nuclear bomb and resting the secret of its construction exclusively in the hands of the USA. His fears were proved by the policy of the Soviet Union which became more and more unfriendly towards the USA and the states of the Western Europe. First of all Attlee aimed at creation of an international organisation for nuclear energy research control and at bringing both Russians and Americans to mutual agreement on that question. He initiated an activity leading to the organisation of conference of the representations of Great Britain, the USA and Canada. It should have made common attitude in nuclear energy control and disclosure of the results of actual research on it. Attlee also would like to prolong the Anglo-American co-operation in technology of production of nuclear weapon research, which existed since the Quebec Agreement in 1943. Clement Attlee, Harry Truman and Wiliam Mackenzie King met in Washington where on November 9-16th 1945 the conference took place. As a result of that meeting the common declaration was proclaimed. It was a compromise between the claims of British Prime Minister and American plan of gradually disclosing of secrets of nuclear weapon production. Washington Declaration found out the necessity of creation of the Atomic Energy Commission as one of the agencies of the United Nations. The Commission should prepare the suggestions concerning: an international exchange of the scientific information, an atomic energy research control, an exclusion of the massive destruction weapon from the armament of the states. The USA also confirmed the necessity of further co-operation concerning atomic energy between the signatories of the Quebec Agreement. Washington Declaration was a success of the diplomacy of Clement Attlee. However it was a fusion of the British conception with the American one, but more important articles of that document were dominated by the political ideas of the British Prime Minister. His efforts allowed Great Britain to gain common control of the nuclear weapon, and in that way the United Kingdom obtained a confirmation of parity in the international policy.